2021
DOI: 10.1007/s00402-021-03982-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of the femoral component orientation on dislocations in THA: a systematic review

Abstract: Introduction Dislocation remains a major complication in total hip arthroplasty (THA), in which femoral component orientation is considered a key parameter. New imaging modalities and definitions on femoral component orientation have been introduced, describing orientation in different planes. This study aims to systematically review the relevance of the different orientation parameters on implant stability. Methods A systematic review was performed accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
0
11
0
1
Order By: Relevance
“…Another important factor that adds to the stability of the hip prosthesis is the position of the femoral component, more specifically the version. A low combined anteversion is associated with posterior dislocation, whereas a high combined anteversion is associated with anterior dislocation [ 15 ]. Due to the ipsilateral knee arthrodesis, a “classic” figure of four positioning of the leg was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor that adds to the stability of the hip prosthesis is the position of the femoral component, more specifically the version. A low combined anteversion is associated with posterior dislocation, whereas a high combined anteversion is associated with anterior dislocation [ 15 ]. Due to the ipsilateral knee arthrodesis, a “classic” figure of four positioning of the leg was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…We hope the data from this study could help to improve the accuracy of surgical navigation systems for total hip arthroplasty (THA) or in the diagnostic work-up of patients with instability after THA, as femoral torsion affects the risk of dislocation and range of motion [38]. Van Correct assessment of femoral torsion is also important when considering a femoral derotational osteotomy, for example in young adults with hip pain due to excessive femoral antetorsion or retrotorsion [4,26], or in patients with malrotation after a diaphyseal femur fracture [24,36].…”
Section: Discussionmentioning
confidence: 99%
“…Reliable assessment of the femoral torsion is not only important for diagnostics and understanding of pathological processes, but also for planning of hip and knee surgery [9,10,38,43]. Femoral torsion assessments are incorporated in three-dimensional (3D) planning software for knee and hip arthroplasty, in which expected values are targeted to obtain optimal femoral component orientation and rotational alignment [20,28].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] To reduce the incidence of dislocation, achieving optimal orientation of the implant placement should be prioritised. 6,7 Intraoperative assessment of dislocation is a simple method for predicting instability after THA. 8 The modular femoral neck system has some practical advantages, allowing for the adjust-Anatomical studies have identified morphological differences in the hip joint between men and women.…”
Section: Introductionmentioning
confidence: 99%